Re-Designing Social Worker Role During World Inflation Spillovers - Ahmed, Dunya (Journal of Ecohumanism, 2024)
Inflation affects vulnerable groups more, governments and NGOs used to support them via social welfare system, where social workers did case studies and ensured fairness. However, with inflation; governments fail to keep up with it, the role of social workers will be more essential and complex. More people will need social workers to be proactive, where there is more need for services and social protection. Methodology is to re-evaluate the criteria of social worker’s role to foresight demands and recommend an international governing guidance. Implication shows the need for re-evaluating to help stabilise families during inflation. A framework is proposed to utilise welfare to support vulnerable groups and social workers’ roles, preparing them for crises such as inflation and having future foresight in social problems.